ANALISIS AKUNTABILITAS LAPORAN REALISASI ANGGARAN DESA SUNGAI BUNDUNG LAUT, KABUPATEN MEMPAWAH, KALIMANTAN BARAT - B1031131100, Muhammad Robby Wahyudi (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
This research is titled the analysis of accountability in budget realization report in Sungai Bundung Laut village, at Mempawah district, Kalimantan Barat. This research was carried about problem in Sungai Bundung village managing thre budgets of the village, because the funds is limited in terms of facilities and infrastructure, so the villagers facing in budget report especially the village budget realization report. The type of analysis in the reaserch is by comparing the budget realization report data of Sungai bundung village in 2015 with the Manual Implementation Guidance of Village Financial Management Consultacy as the Deputy the Deputy that easy to implement and pratical, which has been provided by Departement of financial supervision and Development (BPKP). The results of this research are the online of preparation format of the budget, especially budget realization report in Sungai Bundung, which the preparation is already compatible with the format that has been set from BPKP, however in the Letter payment Request (SPP) of Sungai Bundung village still lach in writing dates and the gone well in this village. Keywords: Accountability ,Accounting, Village Fund.